PENGARUH TEACHER SUPPORT TERHADAP MOTIVASI BELAJAR MELALUI SELF EFFICACY PADA MATA PELAJARAN EKONOMI - Mochtarom, Nabila Rizky Amanda; Fitrayati, Dhiah (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
At SMA Negeri 12 Surabaya, there is a problem related to low student motivation, indicated by the lack of enthusiasm among students in participating in economics subjects. The low learning motivation of these students is predicted to be caused by a lack of teacher support and the students' self-efficacy in learning activities. This study aims to analyze whether teacher support affects learning motivation through students' self-efficacy in economics subjects. The population used in this study was 365 tenth-grade students from SMAN 12 Surabaya, and a sample of 191 students was taken using the Slovin formula. This research uses a quantitative method and a questionnaire as a data collection technique. The data analysis technique used in this study is Structural Equation Modeling (SEM) using WarPLS version 7.0. The results of the study indicate that (1) Teacher Support has a direct effect on learning motivation; (2) Teacher Support has a direct effect on Self-Efficacy; (3) Self-Efficacy has a direct effect on learning motivation, and (4) indirectly, Teacher Support affects learning motivation through Self-Efficacy